Astrocyte as Spatiotemporal Integrating Detector of Neuronal Activity - Gordleeva, Susan Yu.; Ermolaeva, Anastasia V.; Kastalskiy, Innokentiy A.; Kazantsev, Victor B. (Frontiers in Physiology, 2019)
The functional role of astrocyte calcium signaling in brain information processing was intensely debated in recent decades. This interest was motivated by high resolution imaging techniques showing highly developed structure of distal astrocyte processes. Another point was the evidence of bi-directional astrocytic regulation of neuronal activity. To analyze the effects of interplay of calcium signals in processes and in soma mediating correlations between local signals and the cell-level response of the astrocyte we proposed spatially extended model of the astrocyte calcium dynamics. Specifically, we investigated how spatiotemporal properties of Ca2+ dynamics in spatially extended astrocyte model can coordinate (e.g. synchronize) networks of neurons and synapses.